Fiscal and debt policies for the future - Arestis, Philip; Sawyer, Malcolm; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book offers detailed analysis and informed comment on the future of emerging economic policies. It is essential reading for all postgraduates and scholars looking for expert discussion and debate on the issues surrounding economic policy.
Keywords: Economic policy; Macroeconomics; Political economy